Understanding computer systems architecture - Lacy, M. (London : DP Publications, 1991)
The aim of this book is to provide a course text for HNC/D and first or second-year computing degree courses variously called "Computer Systems", "Computer Architecture" and "Computer Technology". It assumes a knowledge of computer hardware and software to approximately GCSE level and offers students the knowledge and skills to consult, with confidence, the advanced texts on this topic. The key concepts which are central to understanding computer systems at HNC/D/degree level are covered, and an "active learning" approach is integral to the book's structure. A free lecturer's supplement in provided
Includes index.
Keywords: Computers system; architecture; Computers